The result of combined cataract surgery with intra ocular lens implantation in advance primary glaucoma - A case report - Suhardjo, Suhardjo (Universitas Gadjah Mada, 1999)
Background: The combined cataract surgery was a procedure by the creation of a new channel for aqueous outflow between the anterior chamber and sub-Tenons space and followed by extracapsular cataract extraction and posterior chamber intra ocular lens implantation. This procedure is relatively new, that the result need to be reported.Objectives: To report the result of combined cataract surgery with intra ocular implantation in advanced primary glaucoma.Methods: A 68-year-old man suffering from senilis cataract and advances glaucoma had combined surgery on the right eye. The combined surgery was effective to control intra ocular pressure, so the glaucaomatous defect was not worsening and visual acuity would be good. The target 10P was reduction of 20-30% 10P or closer to 15 mmHg.Results: The mean post operative intra ocular pressure was normal, but still needed antiglaucoma drugs. Visual acuity was 6/30 cc S + 1.50 cc S +1.50 / C-1.25 with axis 90 to 6/7.5 three months post operative and decreased to 6/15 with the same glasses three years later. With addition of S +3.00 the patient could read a newspaper, however the visual field was slightly worsened.Conclusions: Extra capsular cataract extraction and posterior chamber lens implantation combined with trabeculectomy can improve visual acuity and decrease intra ocular pressure.Key words : advanced glaucoma - combined surgery - target pressure - visual acuity - visual field - anti glaucoma drug.